2016
DOI: 10.14814/phy2.12992
|View full text |Cite
|
Sign up to set email alerts
|

Deep-targeted exon sequencing reveals renal polymorphisms associate with postexercise hypotension among African Americans

Abstract: We found variants from the Angiotensinogen‐Converting Enzyme (ACE), Angiotensin Type 1 Receptor (AGTR1), Aldosterone Synthase (CYP11B2), and Adducin (ADD1) genes exhibited intensity‐dependent associations with the ambulatory blood pressure (BP) response following acute exercise, or postexercise hypotension (PEH). In a validation cohort, we sequenced exons from these genes for their associations with PEH. Obese (30.9 ± 3.6 kg m−2) adults (n = 23; 61% African Americans [AF], 39% Caucasian) 42.0 ± 9.8 years with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 66 publications
3
26
0
1
Order By: Relevance
“…The subjects and data from two previous reports (Pescatello et al. , ) were used in the current study as well. We obtained a blood sample for deep‐targeted exon sequencing and a fasting cardiometabolic profile at the orientation session.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The subjects and data from two previous reports (Pescatello et al. , ) were used in the current study as well. We obtained a blood sample for deep‐targeted exon sequencing and a fasting cardiometabolic profile at the orientation session.…”
Section: Methodsmentioning
confidence: 99%
“…The screening technique has been described in detail previously (Pescatello et al. , ). Briefly, we analyzed genotypic values coded as the number of MA (#MA) for 645 variants from 41 genes (Pescatello et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Montrezol et al showed a reduction on BP in homozygous ACE (I/D) genotypes and no changes in I alleles carriers after a resistance training programme, 18 and Pescatello et al observed the angiotensinogen-converting enzyme (ACE), angiotensin type 1 receptor (AGTR1), aldosterone synthase (CYP11B2), and adducin (ADD1) genes exhibited intensity-dependent associations with the ambulatory BP and postexercise hypotension (PEH) response after acute exercise. 19 However, this effect was observed after vigorous, but not moderate intensity exercise among African Americans.…”
Section: Introductionmentioning
confidence: 97%